Downregulation of miR-26b-5p, miR-204-5p, and miR-497-3p Expression Facilitates Exercise-Induced Physiological Cardiac Hypertrophy by Augmenting Autophagy in Rats - Qi, Jie; Luo, Xue; Ma, Zhichao; Zhang, Bo; Li, Shuyan; Zhang, Jun (Frontiers in Genetics, 2020)
Exercise-induced autophagy is associated with physiological left ventricular hypertrophy (LVH), and a growing body of evidence suggests that miRNAs can regulate autophagy-related genes. However, the precise role of miRNAs in exercise induced autophagy in physiological LVH has not been fully defined. In this study, we investigated the microRNA–autophagy axis in physiological LVH and deciphered the underlying mechanism using a rat swimming exercise model. Rats were assigned to sedentary control (CON) and swimming exercise (EX) groups; those in the latter group completed a 10-week swimming exercise without any load. For in vitro studies, H9C2 cardiomyocyte cell line was stimulated with IGF-1 for hypertrophy. We found a significant increase in autophagy activity in the hearts of rats with exercise-induced physiological hypertrophy, and miRNAs showed a high score in the pathway enriched in autophagy. Moreover, the expression levels of miR-26b-5p, miR-204-5p, and miR-497-3p showed an obvious increase in rat hearts. Adenovirus-mediated overexpression of miR-26b-5p, miR-204-5p, and miR-497-3p markedly attenuated IGF-1-induced hypertrophy in H9C2 cells by suppressing autophagy. Furthermore, miR-26b-5p, miR-204-5p, and miR-497-3p attenuated autophagy in H9C2 cells through targeting ULK1, LC3B and Beclin 1, respectively. Taken together, our results demonstrate that swimming exercise induced physiological LVH, at least in part, by modulating the microRNA–autophagy axis, and that miR-26b-5p, miR-204-5p, and miR-497-3p may help distinguish physiological and pathological LVH.